Understanding Pain Points in Halal Chicken Supply Chains: The Type D Slaughterhouse Experience - Hapsari, Nurul Retno; Rahmawati, Keny; Kasih, Puji Handayani; Leuvano, Raden Achmad Chairdino (RSF Conference Series: Business, Management and Social Sciences, 2025)
This study investigates the pain points of Chicken Halal Supply Chain Management (CHSCM) in Indonesia, with a focus on the experiences of a certified Type D poultry slaughterhouse (RPA) in Yogyakarta. Using a qualitative approach, data were collected through in-depth interviews with a halal academic expert and the RPA operator, and were analyzed thematically against the framework of halal supply chain principles. The findings reveal a persistent gap between regulatory ideals and operational realities. Critical issues include the limited competence of slaughterers, high pre-slaughter mortality during transport, lack of cold chain infrastructure, and unhygienic post-slaughter handling. Certification is perceived by operators as costly and administratively burdensome, while consumer demand remains divided between modern segments that require certification and traditional markets that prioritize affordability and freshness. These pain points not only compromise halal assurance but also pose risks to public health and economic sustainability. The study concludes that targeted interventions, such as structured training, simplified certification procedures, collaborative cold chain solutions, and the adoption of traceability mechanisms, are essential to strengthen halal poultry supply chains in Indonesia.